Sin and its remedy in Paul (James Clarke & Co Ltd, 2022)
Though much-studied, Pauline soteriology can be seen afresh by giving focused attention to the apostle's language and conception of sin. Sometimes Paul appears to present sin and disobedience as transgression, while at other times sin is personified as an enslaving power. Is there a single model or perspective that can account for Paul's conceptual range in his discussion of sin? What does careful study of Paul's letters reveal about the christological and pneumatological remedies to the problem of sin as he conceives of them? These questions are explored in the context of individual Pauline letters, building a richer understanding of the apostle's attitude to sin and its remedy.